The magnetization transfer ratio of the post-mortem canine intervertebral disk is positively correlated to Pfirrmann grading on high field 3.0T MRI: a pilot study - Martenne-Duplan, Antonin; Tricou, Corentin; Finck, Marlène; Cartiaux, Benjamin; Arribarat, Germain; Mogicato, Giovanni (Frontiers in Veterinary Science, 2024)
Objective Intervertebral disk (IVD) degeneration usually occurs earlier in chondrodystrophic dog breeds than in other breeds. Spinal cord compression secondary to IVD degeneration is the most common cause of myelopathy in these dogs. Standard magnetic resonance imaging (MRI) sequences permit the identification of IVD degeneration and its consequences on adjacent neurological structures. In human medicine, quantitative MRI sequences, such as magnetization transfer ratio (MTR) sequences, are developed and used to detect early IVD degeneration. This prospective randomized post-mortem comparative study aimed to evaluate the correlation between a qualitative Pfirrmann MRI grading and the MTR values of the IVD in chondrodystrophic dogs. Materials and methods Vertebral columns of eight canine cadavers were frozen and thawed prior to imaging with T2-weighted and MTR sequences using a 3.0 T high-field MRI. These sequences were reviewed by two observers. A Spearman correlation coefficient was calculated in order to compare the MTR values with the Pfirrmann grade. Pearson correlation coefficients were calculated to evaluate the inter-observer agreement of the delineation of the region of interest (ROI) around the NP and the MTR values. A Wilcoxon-Mann–Whitney test was used to conclude on the significance of the correlation between the MTR values and the Pfirrmann grades. Results There were 138 intervertebral disks analyzed: 29/138 (21.0%) IVD were grade I, 74/138 (53.6%) grade II, and 35/138 (25.4%) grade III. No grades IV and V were present in this study. Inter-observer agreement for delineation of IVD ROI was fair (r = 0.54) but inter-observer agreement of mean MTR value within the ROI was very good (r = 0.89). Mean MTR values were 16.459% (10.0305–21.0950%) for grade I, 18.888% (10.0750–27.2400%) for grade II, and 22.813% (12.5700–31.7600%) for grade III. The mean MTR value was significantly different between each Pfirrmann grade: between grades I and II (p < 0.005), grades II and III (p < 0.05), and grades I and III (p < 0.005). There was a significant moderate positive correlation between Pfirrmann grading and mean MTR values (r = 0.516). Conclusion The magnetization transfer ratio seems to be an objective method to detect early intervertebral disk degeneration via quantitative analysis.